The Effects of HSG Media on Fertility in Unexplained Infertility Cases - Sapmaz, Ekrem; Şimşek, Mehmet; Gürateş, Bilgin; Kumru, Selahattin; Çelik, Hüsnü; Çelik, Aygen; Özcan, Zeynep (Fırat University, 2004)
Objective: Investigation of the effects of liposoluble / watersoluble contrast media used in hysterosalpyngography on fertility in unexplained infertility cases. Material and Method: Sixty primary or secondary infertile cases diagnosed as unexplained infertility were retrieved from the entire infertility cases admitted between June 1998 –March 2001 and they were analyzed by randomized, prospective, single blinded method and classified as the study group (G1=n:30, Lipiodol) and the control group (G2=n:30, Urovision). Hysterosalpyngography was provided two days after the end of menses. The patients who were diagnosed as unexplained infertility and with normal basal clinical and laboratory investigations for infertility have been just monitered for over three months after hysterosalpyngography was done. They were suggested to return back when menstruation delay occur. If pregnancy not achieved over 3 months patients directed for ovulation induction with clomiphene citrate + intrauterine insemination. Statistically Student T test, Mann Whitney U test and X2 were used for continous, ordinal and nominal data, respectively. P value

Amaç: Açıklanamayan infertilite vakalarında histerosalpingografide kullanılan yağda ve suda çözünür ilaçların etkisinin araştırılması. Gereç ve Yöntem: Haziran 1998 - Mart 2001 yılları arasında primer veya sekonder infetilite tanısı almış 60 hasta tek kör, prospektif randomize olarak çalışma grubu (G1=n:30, Lipiodol) ve kontrol grubu olarak (G2=n:30, Urovision) sınıflandırıldı. Menstruasyon bitiminden iki gün sonra bütün hastalara histerosalpingografi uygulandı. İnfertilite araştırması nedeniyle yapılan bazal klinik ve labaratuar tetkikleri normal olan infertil hastalar histerosalpingografi sonrasında 3 ay boyunca takip edildi. Menstruasyon rötarı olanlar gebelik tanısı için çağrıldı. İşlemden 3 ay sonra gebelik elde edilmeyen hastalar klomifen sitrat ile ovulasyon indüksiyonu ve intrauterin inseminasyona yönlendirildi. İstatistiksel hesaplamalar Student T test, Mann Whitney U test ve X2 testleri kullanılarak yapıldı. p
Açıklanmayan İnfertilite Vakalarında HSG'de Kullanılan Ajanların Fertilite Üzerine Etkileri